Transformasi Digital Layanan Akademik Melalui Sistem Informasi Pengajuan Tugas Akhir Online Berbasis Design Science Research - Muhammad Rinov Cuhanazriansyah; Marlina Yuliyanti; Ahmad Aniko Misbakhul Umam; Ayu Miftakhatul Awaliyah (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
The need for increased efficiency, transparency, and quality of academic services is one of the main implications of digital transformation in higher education. This study aims to develop and implement an Online Final Project Submission Information System (SIM Skripsi) as part of efforts to transform digital academic services at IKIP PGRI Bojonegoro. The approach used is Design Science Research (DSR), which includes the stages of problem identification, system design and implementation, and artefact evaluation. The system was developed using Laravel and MySQL with a modular architecture based on microservices and Docker, then tested through trials involving students, supervisors, and academic administration staff. The results of the study show that the implementation of SIM Skripsi significantly accelerated the final project submission process, with an average duration reduction from 7–8 working days to 1–2 working days. The level of user satisfaction, measured using the System Usability Scale (SUS), obtained an average score of 82.4, which is classified as very good, while the system reliability level reached 97.8 per cent. These findings indicate that the Thesis Management System is capable of supporting academic administration efficiency, increasing user acceptance, and strengthening the transparency of the service process. Considering the readiness of technological infrastructure, institutional policy support, and human resource capacity, this system has the potential to be adapted and implemented in other higher education institutions with comparable characteristics. Abstrak Kebutuhan untuk meningkatkan efisiensi, transparansi, dan kualitas layanan akademik merupakan hasil dari transformasi digital di lingkungan pendidikan tinggi. Tujuan penelitian ini adalah untuk mengembangkan dan mengimplementasikan Sistem Informasi Pengajuan Tugas Akhir Online (SIM Skripsi) sebagai bagian dari transformasi akademik digital di IKIP PGRI Bojonegoro. Metodologi yang digunakan adalah Design Science Research (DSR), yang meliputi identifikasi masalah, implementasi sistem menggunakan Laravel dan MySQL, arsitektur sistem berbasis microservices dan Docker, serta evaluasi melalui uji coba kepada mahasiswa, dosen, dan staf administrasi. Temuan penelitian menunjukkan bahwa durasi proses pembelajaran tugas akhir berkurang secara signifikan dari rata-rata 7-8 hari menjadi 1-2 hari. Berdasarkan Skala Usability Sistem (SUS), kepuasan pengguna mencapai skor rata-rata 82,4, yang masuk dalam kategori “sangat baik”, sementara keandalan sistem mencapai 97,8%. Hal ini menunjukkan bahwa implementasi SIM Skripsi dapat meningkatkan proses, meningkatkan kepuasan pengguna, dan meningkatkan transparansi layanan akademik. Melalui optimasi jaringan dan peningkatan fitur tambahan, sistem ini berpotensi untuk diterapkan secara luas oleh perguruan tinggi lainnya.